PELATIHAN PENGELOLAAN AIR BUDIDAYA DAN LIMBAH CANGKANG LOBSTER (LAT) SEBAGAI KERAJINAN DI POKDAKAN MINA MANDIRI DESA JAMBEWANGI, KEC SECANG KAB MAGELANG - Eny Boedi Orbawati; Eric Armando; Firdausa Putra Agry (Universitas Mataram, 2026)
One of the problems faced by freshwater lobster farmers is low survival rates. One way to maintain survival and growth is by managing optimal water quality conditions. The use of groundwater (wells) for cultivation, which tends to have different temperatures compared to outdoor cultivation water, impacts lobster survival during water changes. One of the innovations implemented is the Recirculation Aquaculture System. Stable water quality impacts optimal lobster growth. Lobsters that grow through the molting process become waste that is not properly utilized. This community service activity aims to manage wastewater and lobster shells. This activity was carried out from August to September 2025 at the Mina Mandiri Fish Farming Group (Pokdakan Mina Mandiri) in Jambewangi Village, Secang District, Magelang Regency. The community service participants were 10 members of the Pokdakan, 4 students, and 3 lecturers from Tidar University. The community service material focused on wastewater treatment through Recirculation and the creation of lobster decorations. Based on the material presented to the community groups, lobster shells can have economic value if they are created into decorations by adding various materials, such as frames and sand as a base. Furthermore, efforts to reduce ammonia levels in water are being made using biological filtration using Bucephalandra plants. This training has resulted in increased production and economic growth through effective management of wastewater and shells.